Analisis Pengendalian Kualitas untuk Mengurangi Produk NG Menggunakan QC Seven Tools pada Proses Produksi Injection Molding di Perusahaan Otomotif di Indonesia - Purnomo, Yusup; Pebriani, Rismawati; Nugroho, Ikhsan Dwi; Firmansyah, Vicky Adni; Prastyo, Yudi (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Quality control is an important aspect of maintaining product quality in the manufacturing industry. A high number of defective or Not Good (NG) products can lead to increased production costs as well as decreased efficiency and customer satisfaction. Therefore, an appropriate analysis is needed to identify and reduce the defect rate in the production process. This study aims to analyze quality control efforts in reducing NG products in the injection molding process at an automotive company in Indonesia using the QC Seven Tools method. The data used consisted of 22 days of production data with a total production output of 7,700 pcs and 835 defective products, resulting in a defect rate of 10.84%. The results of the study indicate that the dominant defects are burry (42%) and scratch (30%), which contribute 72% of the total defects. The main causes originate from human and machine factors. The production process is still under control; however, there are variations that need attention. The implementation of QC Seven Tools proved effective in identifying the causes of defects and providing improvement recommendations to enhance product quality.